2022
DOI: 10.1038/s41598-022-24552-4
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement behavior in a real-world virtual reality task reveals ADHD in children

Abstract: Eye movements and other rich data obtained in virtual reality (VR) environments resembling situations where symptoms are manifested could help in the objective detection of various symptoms in clinical conditions. In the present study, 37 children with attention deficit hyperactivity disorder and 36 typically developing controls (9–13 y.o) played a lifelike prospective memory game using head-mounted display with inbuilt 90 Hz eye tracker. Eye movement patterns had prominent group differences, but they were dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 58 publications
4
32
2
Order By: Relevance
“…Group differences between ADHD adults and neurotypical controls: Consistent with the two studies conducted in children (Seesjärvi et al, 2022a;Merzon et al, 2022), we observed that ADHD participants were overall more active in interacting with the virtual environment than controls. In previous studies, we have interpreted higher numbers of actions in ADHD participants to reflect impulsive behavior associated with irrelevant objects, as in the child version much of these extraneous actions relate to interacting with attractive objects (e.g., toys, instruments or devices like TV).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Group differences between ADHD adults and neurotypical controls: Consistent with the two studies conducted in children (Seesjärvi et al, 2022a;Merzon et al, 2022), we observed that ADHD participants were overall more active in interacting with the virtual environment than controls. In previous studies, we have interpreted higher numbers of actions in ADHD participants to reflect impulsive behavior associated with irrelevant objects, as in the child version much of these extraneous actions relate to interacting with attractive objects (e.g., toys, instruments or devices like TV).…”
Section: Discussionsupporting
confidence: 88%
“…In a previous child study with VR goggles, we recorded the gameplay videos and further labeled the actions based on the object salience. However, the group differences appeared not to be explained by stimulus-driven capture of attention (see Merzon et al, 2022). The present findings align with this, as there were group differences also related to exploratory actions that do not specifically relate to object interaction.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations